Perancangan Aplikasi Ujian Online Berbasis Web Study Kasus di STMIK Bina Sarana Global - Julianti, M. Ramaddan; Silalahi, Petrus (JURNAL SISFOTEK GLOBAL, 2015)
At the time of the current era of globalization, technology, information needs in education becomes very in determining the progress of an institution. With the utilization and application of information technology, collection of data relate to each other can be organized into a database file, where the data is organized and stored into the computer to facilitate users in accessing the data. But the use of information technology has not been used as effectively as possible in Bina Sarana STMIK Global. STMIK Bina Sarana Global Cimone Tangerang there are still using manual systems to support the teaching and learning process. Either in the assessment, attendance, and administrative activities, thus requiring a long time to carry out these activities and the results are not necessarily accurate. From this came the desire of the author to make an application Web-Based Online Exam System to support the day-to-day operational activities on the campus. With this web-based application will create an organized data processing, so that the activities of teaching and learning in campus becomes more computerized structured, ease in accessing the data, and delivery of information available.